2018
DOI: 10.3390/nu10040465
|View full text |Cite
|
Sign up to set email alerts
|

A Mediterranean Diet Model in Australia: Strategies for Translating the Traditional Mediterranean Diet into a Multicultural Setting

Abstract: Substantial evidence supports the effect of the Mediterranean Diet (MD) for managing chronic diseases, although trials have been primarily conducted in Mediterranean populations. The efficacy and feasibility of the Mediterranean dietary pattern for the management of chronic diseases has not been extensively evaluated in non-Mediterranean settings. This paper aims to describe the development of a MD model that complies with principles of the traditional MD applied in a multiethnic context. Optimal macronutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 67 publications
(54 reference statements)
1
68
0
Order By: Relevance
“…For example, with increasing tertiles of the MediCul score, there is a significant increase in healthy fats (and ratios of MUFA or total unsaturated fats to SFA), as well as dietary fibre, vitamin C and vitamin E, whereas carbohydrate as percentage energy declines correspondingly, and protein remains the same or decreases slightly. These directions are as anticipated for a ‘traditional’ Mediterranean diet, and macronutrient levels in the third tertile approximate a Mediterranean diet model proposed in Australia ( 50 ) . For example, the macronutrient proportions in the third tertile of MediCul score from the index tool were as follows: fat, 41 % of energy; protein, 15 % of energy; carbohydrate, 36 % of energy; and MUFA, 47 % of total fat.…”
Section: Discussionsupporting
confidence: 81%
“…For example, with increasing tertiles of the MediCul score, there is a significant increase in healthy fats (and ratios of MUFA or total unsaturated fats to SFA), as well as dietary fibre, vitamin C and vitamin E, whereas carbohydrate as percentage energy declines correspondingly, and protein remains the same or decreases slightly. These directions are as anticipated for a ‘traditional’ Mediterranean diet, and macronutrient levels in the third tertile approximate a Mediterranean diet model proposed in Australia ( 50 ) . For example, the macronutrient proportions in the third tertile of MediCul score from the index tool were as follows: fat, 41 % of energy; protein, 15 % of energy; carbohydrate, 36 % of energy; and MUFA, 47 % of total fat.…”
Section: Discussionsupporting
confidence: 81%
“…are consumed in very small amounts and come mostly from nuts, sh, and dairy sources (51,52). Additionally, the Mediterranean diet includes fat comprising between 35% and 45% of energy intake, in which monounsaturated fatty acids (MUFAs) provide at least 50% of total fat content, mostly from the consumption of extra virgin olive oil (51).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, a group of researchers employ a Cretan-based Med Diet protocol in dietary interventions in non-Med Diet populations to assess the effects on metabolic conditions (44)(45)(46) . Recently, this group has published strategies for translating the traditional Med Diet into non-Mediterranean settings, which include meal plans, practical strategies and examples to attain the key principles of the diet with foods that are available and accessible locally (47) . The Healthy Eating Pyramid in Australia (48) incorporates the principles of the Med Diet.…”
Section: Feasibility Of Translating the Mediterranean Diet To An Irismentioning
confidence: 99%
“…A recent study examining the association between dietary cost and adherence to the Med Diet in a UK population found that adherence to the diet was associated with marginally higher dietary cost, but that the potential economic barriers of high adherence would be offset by cost saving from reducing unhealthy food consumption (70) . With many scientific and media reports increasingly being published on the health benefits of the Med Diet (8,9,71) , the key principles and ways of incorporating it into everyday life are becoming more culturally acceptable in non-Mediterranean populations (36)(37)(38)(43)(44)(45)(46)(47)(48)(49)(50)(51) .…”
Section: Proposing a Medéire Food Pyramidmentioning
confidence: 99%